Meat Quality of Japanese Quail (Coutonix Coutonix Japanica) Fed Graded Levels of Fermented Mango Kernel Meal - Kyakma S., Samson; Gibson, Idu; Makir, Wilson (International Journal of Environment, Agriculture and Biotechnology, 2019)
This study is aimed at evaluating the effect of replacing maize with Fermented Mango Kernel Seed Meal(FMKSM) on meat quality of Japanese Quails . A total of two hundred and twenty five (225) one week old unsexed Japanese quails purchased from National Research Institute Vom, Plateau State, Nigeria were used in a six weeks study. The quails were equally allotted in to five treatment group of 45 birds per treatments. The control diet which contains 0% FMSKM and four other experimental diet in which maize was replaced with FMSKM at 10% , 15%, 20% and 25% levels of inclusion thus; 5 treatments respectively. At the end of the experiments, cooking loss, drip loss, Colour and pH were analyzed. From the results, cooking loss, drip loss, Colour and pH showed no significant differences (p>0.05) across treatments. Only water holding capacity at 25% inclusion of FMSKM showed a significant difference (p<0.05) . The result showed that the ater holding capacity remained constant through treatment 1-4 (100%),it then decreased at treatment 5. It was concluded that 20% inclusion of FMSKM is recommended in the feeding of meat type Japanese quail without having any effect on these meat quality parameters.